Variação na composição de espécies arbóreas das florestas alagadas ao longo do Rio Branco, Roraima - Pereira, Lilia Cristina Cruz (2018)
The flooded forest cover 7% of the total area of the Amazon representing the largest zone of flooded forests on the planet. The high precipitation rates, unevenly istributed throughout the year, result in large seasonal fluctuations in the levels of the main Amazonian rivers and their tributaries, which, combined with the low and flat relief, give rise to flood plains, covered by a complex mosaic of habitats that include flooded forests and other successional vegetation types. The Rio Branco is the main drainage system that crosses Roraima from northeast to southwest, passing through three climatic types, defined by a precipitation gradient varying from 1100 to 2300 mm/year, responsible for the transition between savanna-forest vegetation. The flora of the forests flooded by the Rio Branco is still little known and requires ecological studies and quantitative inventories. Environmental changes, whether of natural or anthropogenic origin (eg construction of hydroelectric dams such as those planned for the Rio Branco), may influence the flood regimes and, consequently, alter the structure and floristic composition of the vegetation that accompanies the river. This study aimed to evaluate the changes in the composition of tree species in the seasonally flooded forests along the Rio Branco to provide the baseline for forecasting the effects of environmental changes associated with climate change or infrastructure projects in this biodiversity component (trees). To understand how the composition of tree species responds to the selected environmental factors, we systematically sampled 72 plots of 250 mx 4 m (0.1 hectare) in 12 localities, spanned along 566 km, from the confluence of the Tacutu and Uraricoera rivers to the mouth of the Branco river. In each plot, all the trees and palms with diameter at breast height (DBH) ≥ 10 cm were measured (height and DBH) and identified. We found 3,372 individuals, classified in 56 families, 185 genera and 289 species, 40% of the individuals presented height between 10-20 m with the predominance of individuals with DAP between 10-15 cm. The composition of tree species varied, presenting a species substitution gradiente associated with the precipitation gradient crossed by the river. Therefore, the environmental factors that most explained the distribution of variation in the floristic composition of tree species of the flooded forests of the Rio Branco were precipitation and soil texture. Factors intrinsic to the plants (biotic factors) also should be studied in sets to better understand how the floristic composition changes and can become dissimilar or not with the geographic distance.